FAKTOR-FAKTOR YANG BERHUBUNGAN DENGAN PEMANFAATAN PELAYANAN KESEHATAN DI WILAYAH KERJA PUSKESMAS TAMBARANA KECAMATAN POSO PESISIR UTARA KABUPATEN POSO - Muh Ryman Napirah; Abd Rahman; Agustina Tony (Diponegoro University, 2016)
Community Health Center is a health service facility that organizes public health efforts and the efforts of individual health at the first level, with more prioritizes promotive and preventive efforts, to achieve the highest public health status in its working area. Utilization of Community Health Center service is influenced by several factors like the public perception of health, public perception of the quality of service, family income and level of education. This study aimed to determine the relationship of the public perception of health, public perception of the quality of service, family income and education level with Health Service Utilization in the working area of Community Health Center Tambarana North Coastal of Poso sub-district, Poso district. This type of research was analytical survey research with cross sectional approach. The total of the sample were 69 respondents which was drawn by using Standley Lameshow formula which the population was known. Data was analyzed descriptively which was known as univariate and bivariate analysis, on the credibility degree of 95% (p <0.05). Chi Square test results showed that the public perception of health related to health service utilization (ρ = 0.000), public perception of the quality of service was not related to health service utilization (ρ = 0.213), family income relatedto health service utilization (ρ = 0.004), and there was a relationship between the education level with health service utilization (ρ = 0.000). The relation absence of public perception of service quality with health service utilizationmay be affected by physical evidence, reliability, responsiveness, assurance and empathy.